THE INFLUENCE OF ECOLOGICAL FACTORS ON THE NORMAL GROWTH AND DEVELOPMENT OF GRAPEVINES IN CLIMATE-CHANGED AGRO-LANDSCAPE CONDITIONS - Teona Dolidze (Innovate Conferences, 2025)
Imereti, It is one of the main regions of viticulture in Georgia. The location, relief, local microclimate and favorable soil factors allow for the development of the traditional branch of agriculture - viticulture and the production of various types of high-quality wines. In Georgia, the vine is recognized as a culture of national importance and, taking into account economic factors, interest in it has been growing even more in recent years. However, in order to obtain a final high-quality product, it is necessary to select optimal soil-climatic conditions for growing vines. The climate, relief and soil diversity of the Imereti wine-growing region have historically created excellent conditions for the development of quality viticulture and winemaking, however, the global warming of the climate, unsystematic exploitation of the soil and the extreme conditions caused by these factors that have developed in recent decades have also affected this region and have posed unprecedented challenges to the viticulture sector, as well as other areas of agriculture.
Keywords: vine, bioclimate, soil, agrolandscape.